Headcount forecasting for Customer Experience Department in relation to productivity of an employee - Faruque, Mohammad Nizam Uddin (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.